Osteometabolic and Osteogenetic Pattern of Turkish Immigrants in Germany - Tarner, I. H.; Erkal, M. Z.; Obermayer-Pietsch, B. M.; Hofbauer, L. C.; Bergmann, S.; Goettsch, C.; Madlener, K.; Müller-Ladner, U.; Lange, U. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The etiology of osteoporosis comprises environmental and genetic factors. This study investigated vitamin D deficiency and specific genetic alterations of bone metabolism in a group of 183 Turkish immigrants in Germany in comparison with 46 age and sex matched healthy German controls (females in both groups were pre-menopausal).Bone mineral density (BMD) was measured by dual-energy X-ray absorptiometry. Serum levels of osteologic parameters were determined after overnight fasting. Polymorphisms of the vitamin D receptor (VDR) and lactase genes were genotyped using genomic DNA from peripheral leukocytes. Statistical analysis comprised student’s t-test, Mann-Whitney rank sum test, Chi-square analysis and Fisher’s exact test.Severe 25-OH D3 hypovitaminosis (83.1%) and elevated parathyroid hormone (82%) were common among immigrants. Osteoporosis but not osteopenia was more prevalent in immigrants. Among immigrants with osteoporosis, TRAP5b was elevated in 26.7%, and β-crosslaps in 13.3%. Only the FokI FF VDR-gene-polymorphism was significantly more prevalent among immigrants. In contrast, Ff-genotyped Turkish women exhibited significantly decreased BMD. Lactase polymorphisms were significantly more common among immigrants (84.2% vs. 30.4%) and the CC genotype was commonly associated with reduced BMD (41.6%) but rarely osteoporosis (8.4%).Vitamin D deficiency, secondary hyperparathyroidism and osteoporosis are common among Turkish immigrants in Germany. Thus, in this population osteologic parameters and BMD should be analyzed and deficiencies be treated. Specifically, the VDR gene polymorphism FokI Ff is of clinical value in identifying females at risk of osteoporosis. In contrast, LCT polymorphisms, though common, do not appear to be a risk factor.
Keywords: bone mineral density; osteoporosis; vitamin D deficiency; vitamin D receptor polymorphism; lactase polymorphism